Facio-lingual width of the alveolar base - Wonglamsam Prapart; Manosudprasit Montien; Godfrey Keith (Sciendo, 2003)
Importance is attached to assessment of anterior facio-lingual maxillary and mandibular apical base widths in determining limits to incisor root movements. There is absence of similar assessment of facio-lingual base widths for premolars and molars. The aims of this paper are two-fold: to determine the strength of associations between the facio-lingual widths of the anterior and buccal alveolar apical bases, and to determine if an association might exist between the posterior alveolar base width and specific lateral cephalometric measurements. Comparative measurements were made on 40 adult Thai skulls and their companion mandibles using lateral cephalometric radiographs, linear tomography, and direct measurements of the dento-alveolar and basal structures. Wide variation was found in facio-lingual widths of the alveolar bases. No significant correlations were found between the facio-lingual widths of the anterior and posterior alveolar bases in the maxillae and mandible. Significant inverse correlations were found between the alveolar base widths at the mandibular incisors and the FP-MP and PP-MP angles, and between maxillary incisor base widths and the gonial angle. Importantly, no cephalometric indicators were found to predict posterior alveolar base widths. There is a need to continue to search for assessment indicators.